Numerical solution of a problem on bending oscillation of a rod - M. Bukenov; A. Ibrayev; D. Zhussupova; D. Azimova (Қарағанды университетінің хабаршысы. Математика сериясы, 2017)
In article considered the problem of curved rod fluctuation with Jungs module. Shown the civility of the problem formulation. For solution used integro - interpolation method. Constructed implicit differential scheme, which realized by five - point sweep method. Conducted numerical calculations showed coincidence of theoretical calculation values of solution. Calculations conducted on the system of computer algebra Wolfram Mathematica. Results of calculations are given for two cases of fixing ends of the rod: both ends are fixed and one end is fixed other is free.